The Effect of Premature Birth on The Primary Dentition - Ghada Dh Al - Sayagh; Aisha A. Qasim; Baydaa A Al - Rawi (University of Mosul, College of Dentistry, 2008)
Aims: The aims of the present study were to determine if primary teeth eruption and the presence ofenamel defect are affected by low birth weight and prematurely of birth. Materials and Methods: Thetotal subjects of (420) child aged 4 - 24 months were included in this study, consisted of (210) prematurelyborn (0.05) between differentgenders numbers among in each age group for the preterm and control children. The resultsshowed significantly (p<0.05) delayed eruption of the primary teeth in the prematurely born children ascompared with the control children in all age groups except in 4 - 6 months age group, also there wassignificantly higher percentages of enamel defect present in preterm children, than in control childrenin all age groups except in 4 - 6 months age group. Conclusions: The findings indicated that the eruptionof deciduous teeth was delayed and the percentage of enamel defect was significantly increased inprematurely born children.